Transient Subfoveal Fluid and Visual Loss after Ocriplasmin - Tschuppert, S.; Gerding, H. (Klinische Monatsblätter für Augenheilkunde, 2016)
Background: Intravitreal injection of ocriplasmin for the enzymatic resolution of vitreomacular traction was approved for the EU in 2013. We wish to report our clinical findings and adverse effects that were not observed in the registration trial. Therapy and Outcome: In 5 of our first 12 consecutive cases, resolution of the vitreomacular traction occurred after injecting ocriplasmin. 9 of the 12 patients developed subfoveal fluid, manifest at day 3 post-intervention; this was completely re-absorbed by 6 weeks in 8 of 9 eyes. All 9 cases with subretinal fluid exhibited a significant reduction in mean visual acuity at the first visit, of 0.33 LogMAR (p = 0.008, Wilcoxon signed rank test). After regression of the subretinal fluid, visual acuity returned to the baseline value. Conclusions: In the light of the documented adverse effects of the registration trial, the relatively high rate of subfoveal fluid after injecting ocriplasmin was surprising. Possible causes include enzymatic lysis of the matrix between the outer segments of the photoreceptors and the microvilli of the RPE-cells, or barrier disturbances in the RPE through lysis of the zonulae occludentes.
Keywords: Ocriplasmin; Jetrea; adverse effects; subfoveal fluid; vision loss